Educational software for dyslexic children : a systematic literature review - Ishak, Siti Hafawati; Mohamed Masrop, Noor Azli; Zainuddin, Ghazali; Sahrir, Muhammad Sabri; Syed Sahuri, Sarifah Nurhanum (Faculty of Information & Science Technology, KUIS, 2021)
Educational software nowadays gives something beneficial to the users, especially to the student. Many features in the educational software can help students to learn more and are exciting to do the task. This paper presents how game features are used for dyslexic children in mobile game applications. The purpose of this literature review is to explore the methodology used in research related to educational software for dyslexic children. This methodology used in this paper is adapted from Kencheman and Keele and Petterson. The results show that most of the literature used quantitative methodology in their research. In addition, the studies were more focused on children rather than adult respondents. The literature suggests several software design guidelines for dyslexic children. Most of the educational software discussed in the literature are games, mobile applications and couseware. Findings supported that the use of the application to educate and develop children skills in learning is vital for dyslexic children.